PENGARUH LIKUIDITAS, LEVERAGE DAN PROFITABILITAS, TERHADAP AGRESIVITAS PAJAK (Studi Empiris pada Perusahaan Manufaktur yang termasuk dalam LQ45 pada Bursa Efek Indonesia (BEI) Periode 2013-2017) - Nela Dharmayanti (Universitas Muhammadiyah Tangerang, 2019)
This study aims to examine the influence of liquidity, leverage, and profitability of tax aggressiveness either partially or simultaneously. Independent variables used in this research are liquidity, leverage and profitability. While the dependent variable in this study is the tax aggressiveness measured using the proxy effective tax rate (ETR). The data used in this study is secondary data that is in the form of data obtained from the annual financial statements of companies that have been published by the Indonesia Stock Exchange (BEI). The population in this study amounted to 9 of the Manufacturing companies included in the LQ45 stock index on the Indonesia Stock Exchange (IDX) during the period 2013-2017. The determination of the sample in the study using purposive sampling method and obtain a sample of 8 companies based on certain criteria that have been determined. Data analysis method used in this research is multiple correlation analysis and multiple regression analysis, data processing in this research using elektornik facility that is Microsoft Excel 2010 and SPSS 25.0. The results showed that partially liquidity and leverage variables significantly affect the aggressiveness of taxes. While profitability has no significant effect on tax aggressiveness. The results of research simultaneously show the result that the variable liquidity, leverage and profitability simultaneously affect the aggressiveness of taxes.Keywords : Liquidity, leverage, proftability and aggressiveness of Tax.